EDUKASI PERILAKU PENCEGAHAN BALITA STUNTING DALAM PERSPEKTIF ISLAM - afriyani, Rahmalia; Putinah, Putinah; Fatriansari, Asih; Apriani, Apriani; Desvitasari, Helsy; Desliyanah, Sherly; Syafei, Abdul; Pahrul, Dedi (Ukhuwah : Jurnal Pengabdian Kepada Masyarakat, 2025)
Children with stunting have low intellectual abilities, learning delays, and tend not to graduate from school on time normally. Stunting in childhood has a long-term nature that causes economic levels in the future. Stunting prevention education is important to do. The purpose of this activity was to implement research results to increase public knowledge about stunting prevention behavior in toddlers from an Islamic perspective. This activity was attended by 19 participants and was carried out on November 9, 2023. The results obtained from the educational activities were an increase in the score of stunting prevention behavior before being given education, namely 5.47 ± 1.073, while after receiving education the score of stunting prevention behavior became 8.00 ± 1.491. It was recommended that local officials improve coordination with health workers and health cadres to monitor the health behavior of residents